2003
DOI: 10.1063/1.1631386
|View full text |Cite
|
Sign up to set email alerts
|

Atomic-to-mesoscopic scale structural transition in metal–carbon diamondlike composites probed by second-harmonic generation

Abstract: Structural features of diamondlike metal-doped carbon films are studied by means of optical second-harmonic generation (SHG). A high interfacial sensitivity of the SHG probe and its significant enhancement in metal nanoparticles allows one to distinguish between clusterlike and amorphous atomic scale structure of carbon-metal composites. These films appear to retain a stable amorphous atomic-scale structure in a wide range of metal concentration above the percolation threshold. Atomic-to-mesoscopic scale struc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
3
0

Year Published

2004
2004
2012
2012

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…3(b) shows that the intensity of Raman spectra for Cr doped-DLC film is quite weak relative to the DLC film, which indicates a fairly weak bonding of graphitic phase. This is consistent with the reports of literature, that the C gradually looses its sp 3 type bonding and the DLC network steadily breaks down as the Cr content in the film increases [11][12][13]. Table 1 shows the resistivities and the sheet resistances of Al, DLC and Cr-DLC films.…”
Section: Contents Lists Available At Sciencedirectsupporting
confidence: 93%
“…3(b) shows that the intensity of Raman spectra for Cr doped-DLC film is quite weak relative to the DLC film, which indicates a fairly weak bonding of graphitic phase. This is consistent with the reports of literature, that the C gradually looses its sp 3 type bonding and the DLC network steadily breaks down as the Cr content in the film increases [11][12][13]. Table 1 shows the resistivities and the sheet resistances of Al, DLC and Cr-DLC films.…”
Section: Contents Lists Available At Sciencedirectsupporting
confidence: 93%
“…This will exploit the particular advantages in many fields including electronics, optics, magnetic, and catalysis [1][2][3][4][5][6]. Moreover, many studies showed that the introduction of metallic materials into carbon matrix lowered the compressive stresses and further enhanced the adhesion of the DLC film on substrates [5,6].…”
Section: Introductionmentioning
confidence: 99%
“…Second-harmonic generation ͑SHG͒ has been widely used to study surfaces and interfaces of centrosymmetric semiconductors. [1][2][3][4] For materials with inversion symmetry SHG is electric-dipole forbidden in the bulk, which makes it particularly attractive for this purpose. To facilitate interpretation of SHG data we recently developed a simplified bondhyperpolarizability model ͑SBHM͒ that incorporates the essential physics of SHG, third-͑THG-͒, and fourth-͑FHG-͒ harmonic generation on an atomic scale.…”
mentioning
confidence: 99%